Equilibrium Adsorption of Organic Compounds (Nitrobenzene Derivative, Synthetic Pesticide, Dye, and Surfactant) on Activated Carbon from Single- and Multi-Component Systems - Magdalena Blachnio; Malgorzata Zienkiewicz-Strzalka; Anna Derylo-Marczewska (Molecules)
This work aimed to investigate the adsorption of organic compounds (4-nitroaniline and 4-chlorophenoxyacetic acid) on activated carbon in the presence of selected dyes (uranine and Acid Red 88) and surfactants (sodium dodecyl sulfate and hexadecyltrimethylammonium bromide). The adsorbent, i.e., the activated carbon RIAA (experimental activated carbon, Norit NV, Amersfoort, The Netherlands), was fully characterised by nitrogen adsorption/desorption isotherms, potentiometric titration, small-angle X-ray scattering, X-ray photoelectron spectroscopy, and transmission electron microscopy. The measurements of the adsorption isotherms of individual adsorbates from aqueous solutions were performed, and the Generalised Freundlich equation (GF) was used for their analysis. The influence of the properties of the co-adsorbates and the adsorbent on the efficiency of removal of 4-nitroaniline and 4-chlorophenoxyacetic acid from the water phase was discussed. A sieving effect was found—large dye and surfactant molecules do not penetrate the micropores but only locate at their entrances, limiting the availability of carbon adsorption space for the nitro compound and the pesticide. A very clear influence of the co-adsorbates’ concentration on the adsorption efficiency of the organic pollutants from the mixture was also observed. When the CMC (critical micelle concentration) value was exceeded in the system with surfactant as the co-adsorbent, a decrease in the competition effect on the adsorption of 4-chlorophenoxyacetic acid was observed. This is due to the formation of large aggregates of the surfactant in the solution, which are poorly adsorbed on the activated carbon.